Socio-Economic Impact on Trafficking of Girls/Women for Sexual Exploitation: A Study in Sindhupalchowk District - Shrestha, Anila (NUTA Journal, 2018)
Nepalese society is male dominated society where male holds primary position and female holds secondary position. Many rural poor women/girls work hard at home but their work doesn’t give economic value. They are deprived of education, health, property right and other basic needs. The majority of women are working in informal sector with low paid and even unpaid jobs. So their socio-economic status is very low. The open Nepal-India border is also a responsible factor for girl/women trafficking. It has made traffickers easy to travel across the border and there are several short-cut roads that help traffickers to transport the innocent girls and women because there aren’t security officer in each and every path. But there is a safe environment for the traffickers. Some politician saves them protection if they are arrested. The legal provisions are inadequate in Nepal. There is lack of specific laws related to prostitution and body trade. Lack of political commitment and effective action programs trafficking as a serious crime is increasing day by day. Another factor is low female literacy rate.